Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera) - Raimundi, E.a.; Nascimento, J.m.c.; Barroso, P.c.s.; Hamada, N.; Boldrini, R. (Zootaxa, 2017)
The Serra da Mocidade National Park is a conservation area located in one of the most inaccessible portions of Amazonia Biome in the Roraima State. The first survey of aquatic insects from that in this region was undertaken in January to February 2016 and we present a checklist of eight species of the Leptophlebiidae (Ephemeroptera) found in the Park and describe three new species of Miroculis based on male imagos.